Bureaucratic Performance in the service of Public Complaints in the Social Service Office of Langkat Regency - Dedy Irawadi; Budi Hartono; Maksum Syahri Lubis (Journal of Social Interactions and Humanities, 2024)
Performance is the result achieved by an employee in carrying out their duties and functions as a bureaucratic official. Performance can be used as a measure of the success of an organization or agency in performing its tasks and functions. The current implementation of public complaint services demands prompt resolution from service providers, making it one of the indicators of bureaucratic performance in handling complaints. The aim of this study is to understand and analyze Bureaucratic Performance in public complaint services at the Langkat District Social Office. To achieve this objective, a qualitative method was employed in this research. This study is of a qualitative descriptive nature. Data collection was conducted through interviews, observations, and documentation. The data sources used were both primary and secondary data. The results show that Bureaucratic Performance in public complaint services at the Langkat District Social Office meets the standards of complaint services according to the Performance Theory by Pollit & Bouckaert used in this study. The conclusion drawn from this research is that the bureaucratic performance in public complaint services at the Langkat District Social Office can generally be considered satisfactory and is moving towards an even better level. However, infrastructure and facilities need to be further improved, and officials need to enhance their performance in public complaint services.